(untitled) - CH. Nithin Chakravarthy (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In the present work, The Mechanical and Physical properties of AL-7075 alloy and Inconel-825 alloy and material composition with various applications is seen. So the main content here in this literature survey came to know the methodology of Powder metallurgy process with these materials has noticed. And the following references are seen to use this process.